2006
DOI: 10.1111/j.1365-2133.1983.tb06817.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute non-specific inflammation and modification of macrophage and lymphocyte funtions

Abstract: SUMMARY The acute inflammatory response is a common phenomenon experienced by the physician in a wide variety of clinical situations. One of the major problems facing the investigator in this field of research who wishes to look at the cellular and humoral responses involved, is that in most of the animal models previously used, the inflammatory reaction has been provoked in subcutaneous tissues. Thus, a quantitative assessment of leucocyte emigration and mediator production in the inflamed area is technically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…This suggests that the extravascular compartment, frequently where biomaterials are implanted, will be where CaP‐mediated inflammation is most potent. This is broadly consistent with the studies of crystalline calcium phosphates, which identified the inflammatory effects in vivo ,21, 24 which were independent of complement proteins 22. Furthermore, non‐opsonized crystals were used as an in vitro pathophysiological model 41, 42…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This suggests that the extravascular compartment, frequently where biomaterials are implanted, will be where CaP‐mediated inflammation is most potent. This is broadly consistent with the studies of crystalline calcium phosphates, which identified the inflammatory effects in vivo ,21, 24 which were independent of complement proteins 22. Furthermore, non‐opsonized crystals were used as an in vitro pathophysiological model 41, 42…”
Section: Discussionsupporting
confidence: 80%
“…Hence, these smaller aggregates seem to be most responsible for Nφ activation. This contrasts with the classical crystal phagocytosis studies, where in some, the crystal size is unclear,21, 22 but others used crystals with dimensions comparable to whole cells,32, 43 and the CPPD model used crystals up to 10 μm 24. The size and shape of HA crystals determines the Mφ phagocytic uptake response 30…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation